Protective effect of dapagliflozin against cyclosporine A-induced nephrotoxicity. (2nd November 2022) - Deger, Mutlu; Kaya, Bulent; Akdogan, Nebil; Kaplan, Halil Mahir; Bagir, Emine; Izol, Volkan; Aridogan, Ibrahim Atilla
Abstract: This study aimed to reveal the possible protective effect of dapagliflozin (DAPA) against acute kidney damage due to cyclosporine A (CsA). Thirty-two mice with an eight-week-old Balba̧lbino strain were divided into four groups: control group, CsA group, DAPA group, and CsA + DAPA group. On day 9 of treatment, the animals were decapitated, and bilateral nephrectomy was performed. Oxidative stress and apoptosis were evaluated with caspase-3 activity, total oxidant status (TOS), total antioxidant status (TAS), malondialdehyde (MDA), myeloperoxidase (MPO), B-cell lymphoma-2 (Bcl-2), and Bcl-2-associated X protein (Bax) in the right kidney resection material. The left kidney resection material was evaluated histopathologically. CsA increased caspase-3 activity, Bax, TOS, MDA, TAS, and MPO levels, and the administration of DAPA with CsA significantly reduced this increase in levels ( p < 0.001, p < 0.001, p < 0.001, p < 0.001, p < 0.001, and p < 0.001, respectively). CsA decreased Bcl-2 levels, and administration of CsA + DAPA significantly increased Bcl-2 levels compared with only CsA administration ( p < 0.001). Additionally, administration of DAPA significantly reduced the histopathological findings (parenchymal inflammation, hyaline cast formation, vacuolization, and lysis of renal tubular cells) caused by CsA. DAPA reduces oxidative stress, apoptosis, and histopathological damage caused by CsA in renal tissue.